Development of Interactive Learning Media Based on Articulate Storyline 3 on Newton’s Law Material with a Contextual Approach at the Junior High School Level - Husna, Aminatul; Dinar Maftukh Fajar, Dinar Maftukh (UIN Fatmawati Sukarno Bengkulu, 2022)
Newton’s Law material in science subjects at the junior high school level contains various examples of phenomena and actual applications in everyday life so learning on this material requires a contextual approach and better media in terms of visuals and interactivity. According to several sources, Articulate Storyline 3 is the recommended platform for producing interactive learning media during the COVID-19 pandemic, mainly attractiveness and practicality. This research aims: 1) to describe the validity of interactive learning media based on Articulate Storyline 3 on Newton’s law material with a contextual approach at the junior high school level. 2) to describe students’ responses to interactive learning media based on Articulate Storyline 3 on Newton’s law material with a contextual approach at the junior high school level. This research and development carry on ADDIE stages (Analyze, Design, Develop, Implement, and Evaluate) with subjects including material expert, media expert, user teacher, and 32 students of SMPN 2 Balung, Jember, East Java. The product created is in APK (android package) format with a size of 42.62 MB. This product has a material feasibility level of 4.57 with the “very feasible” category. The media feasibility of 4,80 is included in the “very feasible” category. User eligibility is 4,78 in the “very feasible” category. This media received a positive response from students with a score of 4,00 in the “feasible” category. Overall, the learning media can be determined to be “very valid” for use as a learning medium.